2013
DOI: 10.7482/0003-9438-56-102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time, amount and frequency of feeding on total egg production, fertility and hatchability in broiler breeders

Abstract: Abstract. The effects of timing, the amount and the frequencies of feeding on the performance of broiler breeders (Ross 308) at the age of 31–38 weeks were studied. The broiler breeders were randomly assigned to each of 15 treatments (T). These included day feedings, in which birds were fed once at 4.00 (T1 = control), twice (T2 to T7), thrice a day (T8 to T13) and four (T14 and T15) times per day. The daily feed allotment was divided into different ratios with different time schedules. The nutritional composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
2
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 17 publications
(24 reference statements)
0
5
2
4
Order By: Relevance
“…Feeding time affects egg production, egg quality, reproductive efficiency and oviposition time [25]. [26] reported that the best performance in terms of egg production, fertility and hatchability in broilers was achieved by feeding chickens twice per day with 75% feed at 16.00 and 25% feed at 12.00. [27] reported that egg production was higher in hens fed at midday than in the morning feed.…”
Section: Feeding Timementioning
confidence: 99%
“…Feeding time affects egg production, egg quality, reproductive efficiency and oviposition time [25]. [26] reported that the best performance in terms of egg production, fertility and hatchability in broilers was achieved by feeding chickens twice per day with 75% feed at 16.00 and 25% feed at 12.00. [27] reported that egg production was higher in hens fed at midday than in the morning feed.…”
Section: Feeding Timementioning
confidence: 99%
“…Naast split-feeding is het ook mogelijk om tweemaal daags standaard foktoomvoer te verstrekken, wat in diverse studies is onderzocht. Een hogere eiproductie werd gevonden in vleeskuikenouderdieren bij twice-a-day-feeding (de Avila et al, 2003;Spradley et al, 2008;Taherkhani et al, 2010;Moradi et al, 2013;Soltanmoradi et al, 2013). Er werden echter geen effecten van verschillende voertijdstippen op productie gevonden in de studies van Cave (1981), Bootwalla et al (1983), Samara et al (1996 en Backhouse en Gous (2005).…”
Section: Conclusieunclassified
“…Uit onderzoek van Spradley et al (2008) bleek dat het een-of tweemaal per dag voeren geen effect had op broederijresultaten. Daarentegen vonden Soltanmoradi et al (2013) dat twice-a-day-feeding een hogere bevruchting en uitkomsten gaf. Londero et al (2015) vonden geen effecten van voeren om 08.00 uur (100%), 09.00 en 15.00 uur (50/50%) en 15.00 uur (100%) op bevruchting en uitkomst.…”
Section: Conclusieunclassified
“…In verschillende studies (de Avila et al, 2003;Spradley et al, 2008;Taherkhani et al, 2010;Moradi et al, 2013;Soltanmoradi et al, 2013) vond men dat vleeskuikenouderdieren bij twice a day-feeding een hogere eiproductie hadden in vergelijking met dieren die eenmaal (in de ochtend) werden gevoerd. Geen effecten van verschillende voertijdstippen op productie werden in de studies van Cave (1981), Bootwalla et al (1983) en Samara et al (1996) aangetroffen.…”
Section: Conclusieunclassified